Developing a Logic Model for Evaluating Women's P2P Lending Programs : Pengembangan Logic Model untuk Mengevaluasi Program P2P Lending Perempuan - Primadhita, Yuridistya; Effendi, Jaenal; Purnamadewi, Yeti Lis; Firdaus, Muhammad (EKOMABIS: Jurnal Ekonomi Manajemen Bisnis, 2025)
Financial inclusion remains a significant challenge for women entrepreneurs in Indonesia, particularly in rural areas where access to formal financial institutions is limited. Peer-to-peer (P2P) lending has emerged as an alternative financing solution, with platforms like Amartha pioneering fintech lending specifically for women. Purpose: This study aims to evaluate the effectiveness of women-focused P2P lending programs in enhancing financial inclusion and examine the relationship between inputs, outputs, outcomes, and impacts in the P2P lending model. Methodology: The study employs qualitative analyses by logic model to provide a comprehensive evaluation of Amartha’s women-focused P2P lending program. Findings: This study finds that Amartha's P2P lending model expands women's access to capital and improves their well-being. Originality: This study using the logic model to assess the impact of women-focused P2P lending programs, particularly in terms of inputs, outputs, outcomes, and impacts on women’s economic empowerment and financial inclusion. Inklusi keuangan masih menjadi tantangan besar bagi pelaku usaha perempuan di Indonesia khususnya di daerah pedesaan, dimana akses terhadap lembaga keuangan formal masih terbatas. Peer-to-peer (P2P) lending muncul sebagai solusi alternatif pembiayaan dengan platform seperti Amartha yang memelopori pinjaman fintech khusus untuk perempuan. Tujuan: Penelitian ini bertujuan untuk mengevaluasi efektivitas program P2P lending yang berfokus pada perempuan dalam meningkatkan inklusi keuangan dan menganalisis hubungan antara input, output, outcome, dan dampak P2P lending. Metodologi: Penelitian ini menggunakan analisis kualitatif dengan model logika untuk memberikan evaluasi komprehensif terhadap program pinjaman P2P Amartha yang berfokus pada perempuan. Temuan: Studi ini menemukan bahwa model pinjaman P2P Amartha memperluas akses perempuan terhadap modal dan meningkatkan kesejahteraan. Orisinalitas: Studi ini menggunakan model logika untuk menilai dampak program pinjaman P2P yang berfokus pada perempuan, khususnya dalam hal input, output, outcome, dan dampak terhadap pemberdayaan ekonomi dan inklusi keuangan perempuan.